Design of an Indirect Dryer with Coupling of Solar Collectors and its Thermal Characterization by Drying the Mint Leaves (Mentha spicate) - Téllez, Margarita Castillo; Castillo-Téllez, Beatriz; Gerardo, Alberto Mejía Pérez; Marzoug, Rachid; Álvarez, Diana C. Mex (European Journal of Sustainable Development, 2021)
Man has used solar energy to dry perishable products for many years, managing to preserve a wide variety of foods naturally; drying is a method that highly respects the food’s properties and nutritional content. The consumption of medicinal and aromatic herbs in Mexico is traditional and widespread. In this work, an analysis of an indirect solar dryer’s thermal behavior was carried out with the coupling of solar technologies (water heaters and air collectors and photovoltaic pumping as an aid to the generation of hot air) comparing with electric oven drying in Campeche, Campeche, Mexico. The experimental results showed that the indirect tunnel type dryer that works with evacuated tubes and solar air heater simultaneously is the most efficient technology, with average drying times of 300 min and final humidity of 9.6%. A study of colorimetry, water activity, and drying speed was carried out to control the drying process. It was found that it is possible to use solar energy to dry food as a means of conservation in warm-humid climates, also obtaining significant energy savings and contributing to caring for the environment.